A comparison of the spine posture among several sit-and-reach test protocols - Lopez Minarro, P. A.; Sainz de Baranda Andujara, P.; Rodriguez Garcia, P. L.; Ortega Toro, E. (Journal of Science and Medicine in Sport, 2007)
The purpose of the study was to compare the thoracic and lumbar spine posture among different sit-and-reach tests. Fifty-eight men and 47 women were asked to perform three trials of sit-and-reach test (SR), toe-touch test (TT), back-saver sit-and-reach test (BS) right and left, unilateral seated sit-and-reach test (USR) right and left, and V sit-and-reach test (VSR). Thoracic and lumbar angles were assessed with an inclinometer when subjects reached forward maximally. Women had a lower thoracic angle than men on all tests (p < 0.05). No differences were found in the lumbar angle between genders. The thoracic angle was the highest in VSR (75.3° in men and 65.8° in women) and the lowest in TT (61.7° in men and 53.1° in women). No differences were found among some pairwise comparisons (SR-BS in both genders, SR-TT, SR-VSR and others in women). The VSR test presented the highest values in lumbar spine when compared to other tests (30.5° in men and 32.0° in women). Unilateral seated sit-and-reach test presented the lowest lumbar angle in men (24.2° for right leg and 23.9° for left leg) and women (23.9° in both legs) and there were significant differences with respect to the other tests. Characteristics and administration procedures of tests, such us uni- or bilateral, sitting or standing, measuring with or without box, parallel or V position, and hip position influence thoracic and lumbar postures.